Zasada priorytetu egzekucji nad represją w prawie karnym skarbowym a idea tak zwanej sprawiedliwości naprawczej w powszechnym prawie karnym - Czichy, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The idea of mending justice as the reaction on crime philosophy is recently growing attention of representatives of science and practice. Presented publication tries to answer the question whether it is possible to apply that idea on the basis of fiscal penal law.
Keywords: penal law; execution; represion; fiscal penal law; "mending justice"